Could COVID-19 anosmia and olfactory dysfunction trigger an increased risk of future dementia in patients with ApoE4?. (February 2021) - Manzo, Ciro; Serra-Mestres, Jordi; Isetta, Marco; Castagna, Alberto
Abstract: The association of the coronavirus disease 2019 (COVID-19) with significant neurological and neuropsychiatric complications has been increasingly reported, both during the acute illness and in its aftermath. However, due to the short duration of patient follow up until now, it is not clear whether this infection will be associated with longer-term neurological and/or neuropsychiatric sequelae. In particular, the question of whether COVID-19 will be associated with an increased risk and rate of future dementia remains open and subject to speculation. During the course of the COVID-19 pandemic, an increasing number of patients have reported sudden anosmia or other olfactory dysfunction as concurrent symptoms. The possibility that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) may reach the brain via the olfactory nerve or an upper nasal trancribrial route is an interesting working hypothesis. Among the identified genetic risk factors for Late-onset Alzheimer's disease (LOAD), Apo E4 is one of the strongest and most frequent. People carrying one or two copies of the e4 allele of Apo E4 have significant odor recognition deficits in comparison to those not carrying this haplotype. The hypothesis invoked in this paper is that anosmia/olfactory dysfunctions induced by SARS-CoV-2 may cause an increased a risk of future neurodegenerative dementia in ApoE4 carriers, and that this risk would be higher than in Apo E4 carriers affected by anosmia not induced by SARS-CoV-2. This would be associated with virus-induced chronic modifications in the central nervous system. It is proposed that COVID-19 patients with anosmia and no other serious symptoms should be followed up as part of specifically designed and approved studies in order to identify the early stages of dementia (especially LOAD and Dementia with Lewy Bodies), thereby improving our knowledge of the mechanisms involved in pre-cognitive stages of neurodegenerative dementia and making best use of any available therapies. This latter opportunity is unique and should not be lost.